Profit targets, prospect theory, and earnings management: Evidence from the banking industry in ASEAN - Rahayu, Dewi Puji; Nurkholis, Nurkholis; Subekti, Imam; Atmini, Sari (International Journal of Innovative Research and Scientific Studies, 2025)
This study estimates and analyzes profit targets that motivate managers to engage in earnings management (EM) practices in ASEAN banks. This study uses prospect theory to explain profit targets that motivate managers to engage in EM practices by determining certain thresholds to identify whether banks are practicing EM or not. The approach in this study is quantitative, using data from 74 banks in several ASEAN countries between 2012 and 2024. The data analysis method used in this study is a dummy variable regression model. The results show a significant positive relationship between profit targets and earnings management in several ASEAN countries. The empirical findings indicate that profit targets with a threshold of EPS targets indicate that managers are motivated to engage in EM practices to achieve profit targets. Managers will increase current period profits by borrowing future profits through reducing loan loss provisions. In addition, company size has a positive and significant effect on EM, but profitability has a negative and significant effect. This study also provides evidence that the level of EM practices in the Philippines, Thailand, and Vietnam is lower than in Indonesia.